2021
DOI: 10.1111/tpj.15056
|View full text |Cite
|
Sign up to set email alerts
|

Agromonas: a rapid disease assay for Pseudomonas syringae growth in agroinfiltrated leaves

Abstract: Significance Statement This technical advance introduces a robust and reliable disease assay to monitor bacterial growth of Pseudomonas syringae in agroinfiltrated tissues using an antibiotics cocktail to select against Agrobacterium tumefaciens.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 59 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…To test the possible requirement of Pic3 phosphatase activity in defense, we generated a construct carrying a variant, Pic3NN, with substitutions at the two conserved aspartic residues (D71N and D233N; Figure 2A ). Using the ‘agromonas’ approach (Buscaill et al, 2021), we transiently expressed Pic3, Pic3NN and a YFP control for 2 days in N. benthamiana leaves and then inoculated the plants with DC3000 ΔhopQ1-1, which lacks the T3SS effector gene hopQ1-1 that can be detected by the NLR protein Recognition of XopQ 1 (Roq1), thus making DC3000 ΔhopQ1-1 virulent in N. benthamiana; (Wei et al, 2007; Schultink et al, 2017). Compared to the YFP control, transient expression of wild-type Pic3 significantly increased the DC3000 ΔhopQ1-1 population in N. benthamiana, consistent with Pic3 playing a negative role in resistance to DC3000 ΔhopQ1-1 ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…To test the possible requirement of Pic3 phosphatase activity in defense, we generated a construct carrying a variant, Pic3NN, with substitutions at the two conserved aspartic residues (D71N and D233N; Figure 2A ). Using the ‘agromonas’ approach (Buscaill et al, 2021), we transiently expressed Pic3, Pic3NN and a YFP control for 2 days in N. benthamiana leaves and then inoculated the plants with DC3000 ΔhopQ1-1, which lacks the T3SS effector gene hopQ1-1 that can be detected by the NLR protein Recognition of XopQ 1 (Roq1), thus making DC3000 ΔhopQ1-1 virulent in N. benthamiana; (Wei et al, 2007; Schultink et al, 2017). Compared to the YFP control, transient expression of wild-type Pic3 significantly increased the DC3000 ΔhopQ1-1 population in N. benthamiana, consistent with Pic3 playing a negative role in resistance to DC3000 ΔhopQ1-1 ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…Because depletion of suppressed hydrolases is less likely to cause disease phenotypes, we tested whether increased expression could overcome the suppression and uncover the roles of these hydrolases in immunity. We therefore took advantage of the recently developed ‘agromonas’ assay (Buscaill et al ., 2021 ), which is based on infections of agroinfiltrated tissues with Pto DC3000( ΔhQ ). We cloned and transiently expressed the five selected hydrolases through agroinfiltration and infected the agroinfiltrated leaves 2 d later with Pto DC3000( ΔhQ ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we found that transient overexpression of Nb PR3 results in increased immunity to Pto DC3000( ΔhQ ), confirming that supressed hydrolases may act in immunity. Likewise, we found that transient overexpression of BGAL1 increases bacterial resistance (Buscaill et al ., 2021 ). However, not all suppressed hydrolases reduced bacterial growth upon overexpression in our agromonas assay.…”
Section: Discussionmentioning
confidence: 99%
“…At low bacterial concentrations (OD 600 =0.00001 to 0.0001 for Pto DC3000Q - and OD 600 =0.01 to 0.04 for Agrobacterium), Agrobacterium and Pto DC3000Q - did not interfere with each other, facilitating bacterial pathogen growth assays. Buscaill et al (2021) reported a similar disease assay based on sequential infection of Pto DC3000Q - following Agrobacterium-mediated transient expression in N. benthamiana (Buscaill et al, 2021).…”
Section: Resultsmentioning
confidence: 99%